Characterizing changes in soybean spectral response curves with breeding advancements - Christenson, Brent S.; Schapaugh, William T., Jr.; An, Nan; Price, Kevin P.; Fritz, Allan K. (My University, 2014)
Soybean (Glycine max (L.) Merr.) crop yield has steadily increased in the past 60 yr due in part to breeding advances. Relations between canopy spectral reflectance to specific plant functions may help characterize the impact of breeding on soybean cultivar development. The objectives of this study were to: 1) find specific regions of the soybean canopy spectral reflectance response curves that show genotypic differences; and 2) determine the effect of the breeding process on spectral reflectance response curves of soybean cultivars. Canopy spectral reflectance measurements were taken on 20 maturity group III (MGIII) and 20 maturity group IV (MGIV) soybean cultivars ranging in release year from 1923 to 2010 (arranged in a randomized complete block design) in 2011 and 2012 in Manhattan, KS. Large genotypic differences were found among cultivars, especially in the green (500 nm–600 nm), red (600 nm–700 nm), and red-edge (700nm–730 nm) portions of the spectra. Reflectance in the visible (VIS) (400–700 nm), red-edge (700–730 nm), and near-infrared (NIR) (730–1305) portions of the spectra varied with year of release (YOR) among cultivars. The more recently released cultivars tended to have lower reflectance values in the VIS and red-edge spectra portions and higher values in the NIR portion of the spectra than earlier-released cultivars. Results also indicate that spectral reflectance in the NIR portion of the spectra are highly confounded with maturity and other agronomic traits. These results indicate that breeding advancement has had an impact on canopy spectral reflectance curves and the VIS and red-edge portions of the spectra may be a source of variation for further cultivar development and advancement.
Citation: Christenson, Brent S., William T. Schapaugh, Nan An, Kevin P. Price, and Allan K. Fritz. “Characterizing Changes in Soybean Spectral Response Curves with Breeding Advancements.” Crop Science 54, no. 4 (2014): 1585–97. https://doi.org/10.2135/cropsci2013.08.0575.
Keywords: Soybean; Canopy spectral reflectance; Breeding